Structure-guided engineering of snake toxins for selective modulation of adrenergic and muscarinic receptors - Yixuan Zhong; Huihui Tao; Yu Zhang; Binbin He; Haizhan Jiao; Dandan Wang; Maikun Teng; Hongli Hu; Qiong Guo; Yuyong Tao (Nature Communications)
Abstract Adrenergic receptors (ARs) and muscarinic acetylcholine receptors (mAChRs) are essential G protein-coupled receptors (GPCRs) that regulate a wide range of physiological processes. Despite their significance, developing subtype-selective modulators for these receptors has been a formidable challenge due to the high structural and sequence similarities within their subfamilies. In this study, we elucidated the recognition and regulatory mechanisms of ARs and mAChRs by muscarinic toxin 3 (MT3), a cross-reactive ligand derived from snake venom. By leveraging the distinct toxin-receptor interfaces, we engineer a panel of toxin variants capable of selectively modulating α2A and M4AChR using computational design and directed evolution. These subtype-selective toxins not only provide valuable tools for basic research but also hold therapeutic potential for diseases associated with these GPCRs. This study further underscores the effectiveness of structure-guided approaches in transforming venom-derived scaffolds into receptor-specific modulators.